Left Bundle Branch Block in Suspected Acute Myocardial Infarction: to Early Reperfuse or Not? - Gabrielle Alexander Kartawan (Majalah Kesehatan Indonesia, 2021)
Diagnosing Acute Myocardial Infarction (AMI) in the setting of the Left Bundle Branch Block (LBBB) proposes a great challenge to the clinician. Despite current therapy recommendations, early reperfusion may not be appropriate for all patients with new or presumed new LBBB because only a minority is caused by acute myocardial infarction with true occluded artery. This is a case of a 47-year-old man presented at a rural hospital emergency with highly suspected acute myocardial infarction, a history of old infarct, and LBBB on ECG. Relying on careful clinical examination and close evaluation of hemodynamic with serial ECG, the patient was decided to be managed conservatively. Thorough clinical judgment is required in diagnosing and managing patients with acute MI and LBBB. Avoiding unnecessary burdens and risks resulting from early reperfusion therapy may have a significant impact especially in the centre with limited modality settings.